Paediatric motor difficulties and internalising problems: an integrative review on the environmental stress hypothesis - Erskine, Noah; Barratt, Jaime; Cairney, John (Frontiers in Pediatrics, 2024)
The current study aims to provide an in-depth analysis and extension of the Environmental Stress Hypothesis (ESH) framework, focusing on the complex interplay between poor motor skills and internalising problems like anxiety and depression. Using an integrative research review methodology, this study synthesises findings from 38 articles, both empirical and theoretical, building upon previous foundational works. The hypothesis posits that poor motor skills serve as a primary stressor, leading to internalising problems through various secondary stressors. A rigorous comparison of data was conducted, considering study design, findings, and methodologies—while exploring variables such as age, sex, and comorbidities. The study also enhances the ESH framework by including intrapersonal stressors and introducing resource buffers, including optimism and familial support as additional influencing factors. This multi-level approach yields a more nuanced and comprehensive ESH framework, highlighting the need for future studies to consider variables that intersect across multiple domains and how the relationship between poor motor skills and internalising problems may vary across different life stages.